2020
DOI: 10.3390/foods9040383
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Formaggella della Valle di Scalve Cheese Produced from Cows Reared in Valley Floor Stall or in Mountain Pasture: Fatty Acids Profile and Sensory Properties

Abstract: An important problem in mountain areas is the abandonment of pasture. This trend can be combated by the valorisation of typical dairy products, such as “Formaggella della Valle di Scalve”, a semi-cooked traditional cheese made from whole milk in a mountain area in Italy. The aim of the present research was to compare the fatty acid (FA) profile and the sensory properties of this cheese as manufactured under different conditions: i) from the milk of cows grazing on mountain or valley pasture or fed indoors; ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The level of total CLA varied from 1.06% to 1.85% ( Supplementary Files Table S4), in agreement with data reported for other PDO cheeses produced during grazing period 15,17,48 , when no maize silage is given to cattle. Mean value for CLA (% FA) obtained in our study is more than twice (overall Least Mean Square ± Standard Error Means, 1.48 ±0.05, Figure 6G) respect to plain cheeses, where cattle are fed concentrates 44,47 . For the same reason, similar ndings were noticed for BCFA (overall LMS ± SEM, 3.27 ± 0.05, ( Figure 6C) and n-3 PUFA (overall LMS ± SEM, 0.80 ± 0.05, Figure 6E-F), con rming data of other authors 49,50 .…”
Section: Fatty Acid Compositionmentioning
confidence: 52%
See 1 more Smart Citation
“…The level of total CLA varied from 1.06% to 1.85% ( Supplementary Files Table S4), in agreement with data reported for other PDO cheeses produced during grazing period 15,17,48 , when no maize silage is given to cattle. Mean value for CLA (% FA) obtained in our study is more than twice (overall Least Mean Square ± Standard Error Means, 1.48 ±0.05, Figure 6G) respect to plain cheeses, where cattle are fed concentrates 44,47 . For the same reason, similar ndings were noticed for BCFA (overall LMS ± SEM, 3.27 ± 0.05, ( Figure 6C) and n-3 PUFA (overall LMS ± SEM, 0.80 ± 0.05, Figure 6E-F), con rming data of other authors 49,50 .…”
Section: Fatty Acid Compositionmentioning
confidence: 52%
“…When feeding changes, like along the summer grazing period, a change in fatty acid composition takes place. Several studies were carried out on this aspect, in particular with the aim to compare winter versus summer productions or mountain extensive production versus intensive indoor production [43][44][45][46][47][48] .…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…As a preliminary pre-treatment, the scores for the negative statements of NPI questionnaire [49], of the ATS scale [39], and of the developed scales on FCS and statements on MPP were reversed. For the NPI scale, the statements suggested by the authors were considered negative while, for the ATS scale, we considered four statements (8)(9)(10)(11) of the original scale negative, as they were found to be opposite to the others in an explorative principal component analysis (PCA) map (data not shown). Following the same procedure, of the 18 statements developed for FCS, eight were considered negative (Table 2); while the MPP statements were all considered positive, being true statements extracted from the literature.…”
Section: Analysis Of Questionnaire Datamentioning
confidence: 99%
“…The EU has recognized, for some years, the need to prevent the abandonment of these mountain areas by focusing on the promotion and development of mountain food production as a way to promote sustainable The quality of dairy mountain products starts from the animals, which are moved from indoor feeding with conserved forage to fresh herbage (i.e., feeding on pasture), according to the traditional transhumance system [8]. Several studies have focused on the effects of summer grazing on dairy product characteristics, demonstrating that mountain products are different from indoor feeding products, in terms of sensory attributes [9][10][11][12][13], volatile organic compounds (VOCs)' profile [8,[14][15][16], and fatty acid composition [11,17,18]. The quality of dairy mountain products is also a key aspect for consumers [19], for whom the production of high-quality dairy products is the most important ecosystem service among those provided by summer farms [20].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of rearing conditions on cheese quality . Formaggioni et al [ 13 ] compared the fatty acid profile and the sensory properties of a traditional cheese manufactured from milks of cows reared and fed under different conditions. The experimentation demonstrated that the fat of the cheese obtained from cows fed indoors was richer in medium-chain fatty acids, whereas grazing positively influenced the concentrations of long-chain and unsaturated fatty acids, such as oleic, Conjugated Linoleic Acids (CLAs) and omega 3 fatty acids.…”
mentioning
confidence: 99%